English Competence and Self-Efficacy of Hotel Front-Liners: A Snapshot of Hotel Industry during Pandemic Outbreak - Yerly A. Datu; Iwan Chandra; Carol Linggo Satrio; Isnaini Faridatul Khasanah; Siti Halima (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed at describing the English competence and self-efficacy of hotel front-liners by employing descriptive qualitative research with a case-study as its approach. 14 participants were involved. 50-item test, 10-item self-efficacy questionnaire and 15-item additional questionnaire served as source of information were analyzed on the basis of each category made. Results showed some categories of score range found: ≥80, 70-79, 60-69, 50-59, 50≤. Those with a score range of ≥80 received the highest percentage: 46.2%. Meanwhile, there were at least 23.1% of the participants with a score range of 70-79. A score range of 60-69 received 15.4% of the participants. In the meantime, 7.7% of the participants were in a score range of 50-59. Lastly, it was also found 7.7% of the participants were in a score range of 50≤. For self-efficacy, 4 specific situations were recorded with high percentages. The first was they felt certain to handle their nervousness when facing foreign guests with 69.2%. Secondly, the participants, 69.2%, felt doubtful when applying good organization of ideas. Thirdly, feeling doubtful, 61.5% took place when facing difficult or tough topics with customers. Lastly, 61.5% of the participants experienced the same feeling of doubts as they applied good grammar in their speaking.